Retrospective study on milk production and reproductive performance of dairy cattle in a farm in Selangor, Malaysia - Azhar, H.; Saad, Mohd Zamri; Abdullah, Faez Firdaus Jesse; Salleh, Annas (Indonesian Center for Animal Research and Development, 2016)
Dairy industry is small in Malaysia and unable to fulfill its dairy self-sufficiency. Therefore, Malaysia has to import most of the dairy products to satisfy its domestic demands. This study was performed to evaluate the performance of a selected dairy farm in Malaysia. A dairy farm in Selangor was selected and the farm records between 2011 and 2015 were analysed for the annual milk yield, calving rate and disease occurrence. It was found that the milk yield was low with average annual yield of 44,967 kg and the average milk production per cow per day was 6.83 kg. Clinical mastitis (67%) and traumatic injury (6.9%) were the most common disease occurrence. The calving rate of 75% was within the farm target. Calving percentage and diseases showed significant (P<0.05) positive and negative influences on milk production, respectively.